(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The stability of modern society and the political regime mostly depends on the level of perception of the degree of risk by actors in the political process. The task of the article is to analyze the characteristics of various factors, conditions and circumstances that affect the risk perception by the public and its impact on political stability. The expediency of the problem analysis inthe risk perception by actors of public life is due, that in fact people have different opinions toward the risk theory. The real existence of that fact is presupposedby the necessityin political activity, to analyze possible versions of risk perception by population groups, individuals, political actors of specific risk-based decisions, and in a way or another to assess probabilitis of public reaction for these decisions and their consequences. The study of the specifics ratio of the subjective and objective in the perception of the risk level shows the features and general patterns in the activity of political actors on the one hand, and to identify the place of the "risk perception" problem in technologies for the implementation of the political process, on the other. In political science the study of risk perception makes it possible to evaluate the difference between the level of real risk which were presented by experts and the perceivedrisk’s level that reflects the society reaction based on personal experience and emotional presentation of information. The perceived risk is often a distorted version of actual risk, but in a real political process it is the level that can playdecisive role in bothas negative and positive. The factors impacted on the perception of the risk level have been considered in the article. To solve the problem of the level of risk perception, we will analyze the factors, conditions and circumstances that influence the perception of risk by political actors, by analyzing the reaction of the population to the political decisions of the government of the Republic of Kazakhstan, investigating the impact of information technology and means of influence on the level of risk perception by different population groups. Key words: Political process, stability, perception of risks, factors of risks